A simple two-photon turn-on fluorescent probe for the selective detection of cysteine based on a dual PeT/ICT mechanism. Issue 24 (10th April 2018) - Chen, Xiani; Xu, Hang; Ma, Shengnan; Tong, Hongjuan; Lou, Kaiyan; Wang, Wei
Abstract : N -(6-acyl-2-naphthayl)-maleimide (1 ) is a simple two-photon fluorescent probe with selectivity for cysteine, based on a thiol-Michael-addition-transcyclization cascade and dual PeT/ICT quenching mechanism. Abstract : Herein, a simple two-photon turn-on fluorescent probe, N -(6-acyl-2-naphthayl)-maleimide (1 ), based on a dual PeT/ICT quenching mechanism is reported for the highly sensitive and selective detection of cysteine (Cys) over other biothiols. The probe was applied in the two-photon imaging of Cys in cultured HeLa cells, excited by a near-infrared laser at 690 nm.